Abundance And Diversity Of Ephemeroptera, Plecoptera, Trichoptera (Insecta) In Relation To Environmental Quality Of Upstream Rivers In Kedah, Malaysia - Hamid, Suhaila Ab. (2011)
A relatively rich assemblage of Ephemeroptera, Plecoptera and Trichoptera (EPT) (17,315) (Insecta) immatures were collected from Tupah, Batu Hampar and Teroi rivers in the Gunung Jerai Forest Reserve. From monthly collections starting September 2007 until August 2008 using a kick-net sampling technique, 29 genera representing 19 families of EPT were identified. The EPT community structure and specific sensitivity of EPT genera were not influenced by river water quality (Class I - II of WQI) of which more than 20 taxa were collected from each river. The EPT was most abundant but less diverse in Teroi River while the reverse was recorded from Tupah River.